Schwierigkeiten in Zoom-Lehrveranstaltungen: Beobachtungen, Erklärungsansätze und Lösungsvorschläge - Nicole Robering (IU Internationale Hochschule, 2021)
– Even after several semesters, difficulties are still evident in virtual courses. A common phenomenon is the socalled "black tiles", i.e., students do not use the video function in online courses or use it only very little. This has various effects on the teaching-learning process, which will be examined from different theoretical perspectives. For this purpose, a communication-theoretical, a learning-theoretical, a social-psychological, and a higher education didactic or competence-oriented perspective will be used. The central concern of the article is to understand the phenomenon of non-use of the video function in its effects and to point out possibilities for higher education didactics.
Keywords: 300; Online-Veranstaltungen; Videonutzung; "schwarze Kacheln"; Hochschuldidaktik; Kompetenzorientierung